Validation of the Dépistage Cognitif de Québec in the Oldest Old - Gravel, Amélie (Can Geriatr J, 2020)
OBJECTIVE: We aimed to validate the Dépistage Cognitif de Québec (DCQ; www.dcqtest.org), a new cognitive screening tool for atypical degenerative syndromes, in the oldest old. METHODS: The DCQ was developed by expert behavioural neurologists and clinical neuropsychologists based on updated criteria for Alzheimer’s disease, primary progressive aphasia, and behavioural variant frontotemporal dementia. It targets five relevant cognitive domains: Memory, Visuospatial, Executive, Language, and Behaviour. Validation was performed using a prospective community-based sample consisting of 53 healthy French-speaking Canadian volunteers aged between 80 and 94 years old. Normative data were derived from participants with no history of cognitive difficulties and a Montreal Cognitive Assessment (MoCA) score ≥ 24. RESULTS: The mean DCQ total score (out of 100) was 84.65 (SD = 6.33). Pearson’s correlation coefficient showed a moderate, but significant, correlation (r = 0.36, p < .01) with the MoCA. Normative data shown in percentiles were stratified by age and education for DCQ total score and for each of the five cognitive domains. CONCLUSIONS: This study suggests that the DCQ is a valid cognitive screening test in the oldest old. It is proposed that the DCQ can help early identification of atypical degenerative syndromes.